Progress in providing legal abortion services after law reform: A quantitative study in three provinces of Argentina. - Sarah C Keogh; Georgina Binstock; Mailén Pérez Tort; Susheela Singh (PLOS Global Public Health)
Argentina's 2021 abortion law grants the right to abortion on-request up to 14 weeks' gestation, as well as continuing to allow abortion after 14 weeks on specific grounds. The early years after law reform provide a unique opportunity to assess progress and identify barriers, to both inform program improvements and guide other countries undergoing reform. This study assesses the first two years of law implementation. We surveyed a purposive sample of 45 key informants about implementation successes and barriers. In addition, we surveyed 223 public health facilities (selected through stratified systematic random sampling) in three provinces: Buenos Aires, Chaco and La Rioja. We collected information on abortion services, resources, personnel, training, and obstacles to provision. We present weighted results on characteristics of abortion provision by facilities, representative of each province, complemented by key informant perspectives. Two years into law reform, abortions under 14 weeks were offered in a large number of facilities at all levels, while later abortions were offered mainly in hospitals. Facilities adhered to protocols, had adequate supplies, and kept comprehensive records. Over 90% of abortions were performed using misoprostol, with MVA accounting for most of the remainder. Major barriers to provision included insufficient personnel, exacerbated by high levels of conscientious objection (over 60% of hospitals had at least 2 objecting doctors), and inadequate training in methods other than misoprostol, particularly among health centers. Argentina has made impressive advances in the short time since law reform. Implementation could be improved by increasing personnel (through incentives, task-shifting, and enforcement of conscientious objection regulations), strengthening training on different abortion techniques, and expanding public information campaigns about abortion rights and services available. In the face of diminished support for abortion under the new government, measures to strengthen abortion services and reduce stigma are critical, if reproductive rights are to be upheld.